miR‐126‐3p is essential for CXCL12‐induced angiogenesis - Bassand, Kévin; Metzinger, Laurent; Naïm, Meriem; Mouhoubi, Nesrine; Haddad, Oualid; Assoun, Vincent; Zaïdi, Naïma; Sainte‐Catherine, Odile; Butt, Amena; Guyot, Erwan; Oudar, Olivier; Laguillier‐Morizot, Christelle; et al. (Journal of cellular and molecular medicine, 2021)
Atherosclerosis, in the ultimate stage of cardiovascular diseases, causes an obstruction of vessels leading to ischemia and finally to necrosis. To restore vascularization and tissue regeneration, stimulation of angiogenesis is necessary. Chemokines and microRNAs (miR) were studied as pro‐angiogenic agents. We analysed the miR‐126/CXCL12 axis and compared impacts of both miR‐126‐3p and miR‐126‐5p strands effects in CXCL12‐induced angiogenesis. Indeed, the two strands of miR‐126 were previously shown to be active but were never compared together in the same experimental conditions regarding their differential functions in angiogenesis. In this study, we analysed the 2D‐angiogenesis and the migration assays in HUVEC in vitro and in rat's aortic rings ex vivo, both transfected with premiR‐126‐3p/‐5p or antimiR‐126‐3p/‐5p strands and stimulated with CXCL12. First, we showed that CXCL12 had pro‐angiogenic effects in vitro and ex vivo associated with overexpression of miR‐126‐3p in HUVEC and rat's aortas. Second, we showed that 2D‐angiogenesis and migration induced by CXCL12 was abolished in vitro and ex vivo after miR‐126‐3p inhibition. Finally, we observed that SPRED‐1 (one of miR‐126‐3p targets) was inhibited after CXCL12 treatment in HUVEC leading to improvement of CXCL12 pro‐angiogenic potential in vitro. Our results proved for the first time: 1‐the role of CXCL12 in modulation of miR‐126 expression; 2‐the involvement of miR‐126 in CXCL12 pro‐angiogenic effects; 3‐the involvement of SPRED‐1 in angiogenesis induced by miR‐126/CXCL12 axis.